2009
DOI: 10.1007/s00404-009-1310-y
|View full text |Cite
|
Sign up to set email alerts
|

Inhibin/activin-betaC and -betaE subunits in the Ishikawa human endometrial adenocarcinoma cell line

Abstract: Here, we show for the first time that the novel inhibin/activin-betaC and -betaE subunits are expressed in normal human endometrium and the estrogen receptor positive human endometrial carcinoma cell line Ishikawa using RT-PCR and immunohistochemical detection methods. Interestingly, the Ishikawa minus cell line (lacking estrogen receptor expression) demonstrated no to minimal expression of the betaC subunit as observed with immunofluorescence and RT-PCR, suggesting a possible hormone- dependency of this subun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…The inhibin βC protein was primarily expressed in human liver and prostate [27], while inhibin/activin βE mRNA was predominantly synthesized in human liver with low levels found in heart, testis, leukocytes, and skeletal muscle [5]. Inhibin βC was previously detected by immunohistochemical methods in normal and abnormal placenta [28,29], endometrial cell lines [30,31], endometrial cancer [32], and cervical tissue [33]. Additionally, the inhibin βE is synthesized in normal and abnormal placenta [5,34,35] as well as human cervical tissue [36] and the endometrial cancer cell line Ishikawa [31].…”
Section: Introductionmentioning
confidence: 99%
“…The inhibin βC protein was primarily expressed in human liver and prostate [27], while inhibin/activin βE mRNA was predominantly synthesized in human liver with low levels found in heart, testis, leukocytes, and skeletal muscle [5]. Inhibin βC was previously detected by immunohistochemical methods in normal and abnormal placenta [28,29], endometrial cell lines [30,31], endometrial cancer [32], and cervical tissue [33]. Additionally, the inhibin βE is synthesized in normal and abnormal placenta [5,34,35] as well as human cervical tissue [36] and the endometrial cancer cell line Ishikawa [31].…”
Section: Introductionmentioning
confidence: 99%
“…HEC-1A and HEC-1B; Ishikawa plus and Ishikawa minus) (41,44). Several inhibin-subunits have been observed in the Ishikawa and RL95-2 cell lines by using immunohistochemical techniques (35,70,71). In this study, inhibin-· synthesis was demonstrated in several endometrial cancer cell lines by using immunohistochemical and molecular biological techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The endometrial cancer cell lines Ishikawa plus (estrogen receptor positive), Ishikawa minus (estrogen receptor negative), HEC-1A, HEC-1B, and RL95-2 were obtained from ATCC (LGC Promochem GmbH, Wesel, Germany) and were grown in Quantum 263 medium (PAA, Pasching, Austria), supplemented with antibiotics at 37°C in a humidified atmosphere with 5% CO 2 as previously described (34,35).…”
Section: Methodsmentioning
confidence: 99%
“…Nonspecific binding was blocked by incubating the sections with Ultra V Block (Lab Vision) for 15 minutes at room temperature as previously described. 9,13 Thereafter, slides were incubated with inhibin-A A antibody (1:100 in dilution medium; DAKO) or inhibin-A B antibody (1:10 in dilution medium; DAKO) overnight at 4-C, followed by a 1:500 diluted Cy3-conjugated goat-antimouse antibody (Dianova, Hamburg, Germany) for 30 minutes in room temperature. The slides were finally embedded in a mounting buffer containing 4,6-diamino-2-phenylindole, resulting in blue staining of the nuclei.…”
Section: Cells and Cell Culturementioning
confidence: 99%